1977
DOI: 10.1073/pnas.74.9.3677
|View full text |Cite
|
Sign up to set email alerts
|

Poliovirus-specific primer-dependent RNA polymerase able to copy poly(A).

Abstract: A template-dependent RNA polymerase has been isolated from poliovirus-infected cells by assaying for the ability of the enzyme to copy pOly(A) complexed to an oligo(U) primer. The polymerase was solubilized with detergent, and RNA was removed by precipitation with 2 M LiCI. The solubilized polymerase required both poly(A) and ofigo(U) for activity and was stimulated by Mg2+ but was inhibited by Mn2+. Poly(A) * oligo(U)dependent DlyU) polymerase was not found in extracts of HeLa cells until about 2 hr after pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
127
0
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 21 publications
7
127
0
1
Order By: Relevance
“…Determination of RNA polymerase activity in these extracts was as described previously (Flanegan & Baltimore, 1977;van Bokhoven et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Determination of RNA polymerase activity in these extracts was as described previously (Flanegan & Baltimore, 1977;van Bokhoven et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…To the extent that these activities in plants or at least their sometimes very great increase was attributed to a virus, they were expected to be more or less specific in requiring that viral RNA as template. This is the case for the bacterial and animal RNA virus replicases (19,20). However, the plant virologists were uniformly disappointed, in that their solubilized enzymes would accept any RNA and many polynucleotides as templates.…”
mentioning
confidence: 99%
“…This virus resembles the animal picornaviruses in many regards and has even more RNA than these viruses, which definitely code for their specific RNA polymerase (20,23). Without doubt viral genes are involved in eliciting the increased production ofplant enzymes, and in two divided-genome viruses we know that these genes are on the larger RNA [more than 2 x 106 daltons in cowpea mosaic virus (24) and tobacco rattle virus (25)].…”
mentioning
confidence: 99%
“…Purified FMDV RNA polymerase is capable of initiating RNA synthesis in vitro on an FMDV RNA template. The enzyme also tran-scribes in vitro the synthetic template poly(A) primed with (Up)5U with a poly(U) polymerase activity (6). Biochemical mapping of FMDV-coded proteins with pactamycin has shown that P56a is encoded by a region close to the 3' end of the genome (7,8).…”
mentioning
confidence: 99%